Behavior of visual inspection with acetate acid (VIA) test on women - Sri Dewi Handayani; Nanik Setiyawati; Dyah Noviawati Setya Arum (Poltekkes Kemenkes Yogyakarta, 2018)
Every year according to WHO (World Health Organization), 490.000 women in the world are diagnosed with cervical cancer. The incidence of cervical cancer can be prevented by early detection, one of which is by VIA test. However, coverage of VIA in Central Bangka in Koba District is still very low. ie 3.25%. Knowing the factors that most influence the behavior of VIA test. This research uses an analytical survey method with a cross-sectional approach. Population in this research is women of reproductive age who are married as many as 64 respondents. Data analysis techniques use chi-square, Fisher exact test, and logistic regression. The behavior of VIA test is still low (23,4%). The result of bivariate analysis of the degree of confidence (CI) 95% obtained the significant relationship between, education (p-value =0,003), knowledge (p-value =0,000), access information (p-value =0,001), and support of community health worker s (p-value =0.001) with VIA test behavior. While age (p-value =0,637), parity (p-value =0,220), and husband / family support (p-value = 0,353. The most influential factor on VIA test behavior is community health worker support (PR =11.6 with 95% CI value (1,621-83,026)). The result of the logistic regression test obtained that together probability mother to do an examination of VIA if have higher education, got community health worker support, and supportive attitude is 22,05%. Majority of respondents are high risk aged, low education, low-risk parity, lack of knowledge, support, and access to information, get support from their husbands/families and get support from community health worker s. There is a significant relationship between education, knowledge, attitudes, access to information, and community health worker support for VIA test behavior. The most influential factor in the behavior of VIA test is the support of community health workers.